Rastreabilidade bovina utilizando identificação por radiofrequência em pecuária de precisão modelo teórico - Borne Junior, José Ayrton de Souza (2015)
This paper presents a theoretical model of electronic technology applied to Precision Farming and becomes a grant to further increase the use of Precision Farming, setting that is transforming the way you get the results from the works in the field. The design of a radio frequency identification system, currently known as RFID, to be used in the identification and traceability of cattle is the goal to be achieved. It seeks initially emphasize the definition and the use of the use of Precision Farming as a routine in the activities of the field in Brazil. How is the cattle industry and the Precision Farming definition are important items to achieve the proposed goal. The SISBOV system and traceability are presented, showing its importance, but not the obligation deployment along to landowners who work with the creation and marketing of cattle and their meat products. Shows the definition of microprocessors and microcontrollers, their internal architectures and all the associated peripherals to them and is also shown as the definition of embedded systems has made a revolution in the design of these. Plot a marketing scenario and use of electronic products in the Brazilian commercial sphere, indicating how the delay in using technology more turns in the electronics consumers than in technology trainers. Emphasizes in the principle of operation of RFID systems and which the communication protocols that are used. The reader RFID design and miniaturization of electronics has enabled the creation of a device with surface mount technology decreasing the dimensions of the printed circuit board and allowing the reduction of cost in the design of this system. We present all the peripherals that make it up and the way they connect with the master processor, including the slave processor which performs the digital input and output functions and the keyboard. Communication protocols and flowcharts show the use of known commercial channels in using software. The use of solar energy is presented as an alternative source of electric power supply in the operation of the reader equipment. The high cost of commercial RFID modules prevented the practical implementation of the system.